THE FINTECH REVOLUTION: ANALYZING KEY INNOVATIONS RESHAPING THE FUTURE OF BANKING AND FINANCE - Sudheer Chennuri; Shishir Biyyala; Phanindra Kalva, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article examines the transformative impact of fintech innovations on the banking industry and broader financial services sector. By analyzing five key technological advancements—Generative AI, Open Banking, Quantum Computing, Behavioral Biometrics, and RegTech—we explore how these innovations are reshaping operational models, decision-making processes, and customer experiences in finance. The article highlights how advances in data connectivity and cost-effective computing have fostered more inclusive and efficient markets while simultaneously posing significant challenges for regulators. We argue that these fintech innovations are not only redefining customer relationships and market structures but also necessitating a delicate balance between fostering innovation and ensuring financial stability, data privacy, and consumer protection. The article concludes by discussing the future prospects of fintech, emphasizing the need for adaptive regulation to keep pace with rapid technological advancements in the financial sector. Our findings contribute to the growing body of literature on digital transformation in finance and provide insights for policymakers, financial institutions, and technology providers navigating this dynamic landscape.